Mechanical properties of a photosensitive resin structure - ZHU Dong-mei; DING Feng; LIU Hai-ping; LIU Guo-yong (工程科学学报)
A 3D printing photosensitive resin structure has many advantages, such as good corrosion resistance, flexibility, low yield, and superior deformability; thus, it has been widely used in several fields.In this study, a new photosensitive resin structure was designed and built using 3D printing method.The new photosensitive resin structure is mainly used as a damping element in shockabsorbing and -isolating composite structures.First, load-displacement curves were obtained by compression experiments using the universal testing machine controlled via a microcomputer, and the equivalent elastic modulus of the specific points in the structure was calculated.Dynamic loading tests were conducted using the fatigue machine.Moreover, the hysteresis loops under different frequencies between 5 Hz and 20 Hz were obtained.The equivalent damping ratio was calculated on the basis of the hysteresis loops.The static and dynamic calculation models were built on the basis of the finite element method.After the calculations, the numerical results and the test data under the same conditions were compared.The numerical results agreed well with the test data, thereby verifying the feasibility of the finite element models.Furthermore, the influences of different geometric parameters, such as slot width, inner arc, outer arc, and thickness, on the equivalent elastic modulus of the specific location and equivalent damping ratio of photosensitive resin were investigated by the finite element method.When the 3D printing photosensitive resin structure is subjected to force, it maintains a stiffness output and small deformation along the longitudinal direction; however, the lateral displacement can be enlarged.The 3D printing photosensitive resin structure has a good capability to reduce vibration and resist deformation.The results provide references for the future research of the static and dynamic characteristics and engineering application of the 3D printing photosensitive resin structure.